Chemical Vapor Deposition Synthesis of Ultrathin Hexagonal ReSe2 Flakes for Anisotropic Raman Property and Optoelectronic Application. Issue 37 (8th July 2016) - Hafeez, Muhammad; Gan, Lin; Li, Huiqiao; Ma, Ying; Zhai, Tianyou
Abstract : Hexagonal crystalline ultrathin ReSe2 flakes are synthesized for the first time by a chemical vapor deposition (CVD) method. The as‐synthesized ReSe2 flake is revealed as a novel structure, which has mirror‐symmetric single‐crystal domains inside, by polarization incident Raman and HRTEM. The successful development of the CVD method will facilitate research on the novel anisotropic electronic/optoelectronic properties of ReSe2 in the future.